An investigation of prevalence of codependent personalities who enter nursing rather than other health care-related fields. - Ridley JW (Investigation of Prevalence of Codependent Personalities Who Enter Nursing Rather Than Other Health Care-related Fields, 1993)
Codependency is a set of personality traits that characterize the lives of certain people. It is commonly believed that those in the caring professions more often exhibit the traits of codependency than those in other professions. This study was performed in order to determine if there is a difference between non-medical and medical personnel. Medical personnel in this study included medical professionals other than nurses, and a nurse group which was composed of LPN's, RN's, and staff and administrative personnel. The Spann-Fischer Codependency Scale was administered to groups of medical personnel in six geographic locations. The mean score from this scale was used to compare medical with non-medical personnel for differences in degrees of codependency. Comparisons were then made within the medical groups, using comparisons regarding gender, age ranges, RN's and LPN's, administrative nurses and staff nurses, racial differences, educational levels in nursing, and total years in the nursing profession. Some significant differences were found in this study. Raw scores of all medical personnel were somewhat higher than those of non-medical professionals, when averaged. Medical personnel who are not nurses showed a codependent rate similar differences exist between RN's and LPN's, with LPN's scoring significantly higher on the codependency scale. Staff nurses also scored higher in codependency when compared with the mean scores of the administrative nurses. In conclusion, the field that a person is in has a relationship with being codependent. This study does not consider whether the subjects were codependent prior to entering the medical profession. It also does not attempt to determine if the subjects became more codependent by fulfilling their own needs, when dealing with patients who have obvious health problems. Three significant findings from this study leads to a need for further research on the subject of codependency as it relates to the medical profession. Longitudinal studies should be conducted, performing analyses of codependence for those entering the medical professions, another analysis in the last year of education and training, as well as a final one a period of time after entering into the profession as a practitioner of a particular medical skill.